2009
DOI: 10.2340/16501977-0378
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic characteristics of shoulder rotators in patients with adhesive capsulitis

Abstract: High-speed external rotator strength and isometric internal rotator strength of the affected shoulders were decreased significantly. Isokinetic exercise may not increase the resting muscle activities and co-activity. These results provide a reference in planning muscle strengthening programmes and goals for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Because most functional activities are dynamic, evaluating isokinetic shoulder strength may be more appropriate when relating strength to functional performance and clinical outcome. However, data for isokinetic strength measurements around the shoulder are available only for normal healthy subjects [7], patients after open fixation of glenoid rim fractures [33], open [1, 10] and arthroscopic anterior stabilization [15, 21], rotator cuff surgery [4, 11, 14, 34, 43], with adhesive capsulitis [26, 27, 41], subacromial impingement [16, 24, 30], and pectoralis major muscle rupture [17], but not for patients with a reverse shoulder prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Because most functional activities are dynamic, evaluating isokinetic shoulder strength may be more appropriate when relating strength to functional performance and clinical outcome. However, data for isokinetic strength measurements around the shoulder are available only for normal healthy subjects [7], patients after open fixation of glenoid rim fractures [33], open [1, 10] and arthroscopic anterior stabilization [15, 21], rotator cuff surgery [4, 11, 14, 34, 43], with adhesive capsulitis [26, 27, 41], subacromial impingement [16, 24, 30], and pectoralis major muscle rupture [17], but not for patients with a reverse shoulder prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…FSS patients have an increasingly severe shoulder pain and localized discomfort near the insertion of the deltoid muscle, limitation and pain in the active range of motion (AROM) and passive range of motion (PROM) especially in elevation and external rotation, and diminishing shoulder function in the sixth decade of life [27]. Shoulder girdle muscle strength has been found to be decreased in FSS patients [14,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that 5–6 weeks of immobilization facilitated a significant decrease in muscle strength and cross-sectional fiber areas ( 8 ). Moreover, muscle strength of the external rotators in the shoulders affected by adhesive capsulitis significantly declined ( 9 ). Rotator cuff strengthening exercises have shown positive effects on improving the range of motion and functional outcome ( 10 ).…”
Section: Introductionmentioning
confidence: 99%